Life Cycle Carbon Emission Analysis of Buildings with Different Exterior Wall Types Based on BIM Technology - Yuelong Lyu; Nikita Igorevich Fomin; Shuailong Li; Wentao Hu; Shuoting Xiao; Yue Huang; Chong Liu (Buildings)
Building energy conservation and emission reduction are crucial in addressing global climate change. High-performance insulated building envelopes can significantly reduce energy consumption over a building’s lifecycle. However, few studies have systematically analyzed carbon reduction potential through a life cycle assessment (LCA), incorporating case studies and regional differences. To address this, this study establishes an LCA carbon emission calculation model using Building Information Modeling (BIM) technology and the carbon emission coefficient method. We examined four residential buildings in China’s cold regions and hot summer–cold winter regions, utilizing prefabricated concrete sandwich insulation exterior walls (PCSB) and autoclaved aerated concrete block self-insulating exterior walls (AACB). Results indicate that emissions during the operational phase account for 75% of total lifecycle emissions, with heating, ventilation, and air conditioning systems contributing over 50%. Compared to AACB, PCSB reduces lifecycle carbon emissions by 18.54% and by 20.02% in hot summer–cold winter regions. The findings demonstrate that PCSB offers significant energy-saving and emission-reduction benefits during the construction and operation phases. However, it exhibits higher energy consumption during the materialization and demolition phases. This study provides a practical LCA carbon calculation framework that offers insights into reducing lifecycle carbon emissions, thereby guiding sustainable building design.